1968
DOI: 10.1017/s0021859600017160
|View full text |Cite
|
Sign up to set email alerts
|

Copper deficiency in crops in north-east Scotland

Abstract: SummeryField and pot experiments were carried out to determine how copper deficiency can be corrected on some soils in north-east Scotland. Spring-sown oats and barley are more susceptible to this deficiency than mixed herbage, while potatoes and swedes have not responded to Cu. The deficiency can be corrected by applying 10–20 lb CuSO4.5H2O per acre to the soil. Both field and pot experiments show that such treatments have large residual effects and under field conditions are effective for at least 8 years. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1975
1975
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Copper deficiency in spring-sown cereals has been reported on soils of the Boyndie, Corby, Countesswells, Ordley and Elgin series (Reith, 1968(Reith, , 1976. These soils are developed on sands, granite or a mixture of sands and schists and contain between 2 and 15 mg/kg total copper.…”
Section: Total Copper In Relation To Problems Of Deficiency or Excessmentioning
confidence: 99%
“…Copper deficiency in spring-sown cereals has been reported on soils of the Boyndie, Corby, Countesswells, Ordley and Elgin series (Reith, 1968(Reith, , 1976. These soils are developed on sands, granite or a mixture of sands and schists and contain between 2 and 15 mg/kg total copper.…”
Section: Total Copper In Relation To Problems Of Deficiency or Excessmentioning
confidence: 99%
“…(1979). Significant correlations between 1956Henriksen & Jensen, 1958Alston & McConaghy, 1965McKenzie, 1966Reith, 1968Beyers & Hammond, 1971Brogan et al, 1973Osiname et al, 1973King & Alston, 1975Archer, 1980Jarvis & Whitehead, 1981 McBratney et af., 1982Sillanpaa, 1982Tills & Alloway, 1983Dickson & Stevens, 1983 This study * Expressed as mg 1…”
Section: Discussionmentioning
confidence: 99%
“…A critical concentration of 0.75 mg kg-' EDTA-extractable Cu has been reported as a result of field experiments on a range of soils in Scotland by Reith (1968), while McKenzie (1966) found that only two out of 29 Cu-deficient soils had EDTA-extractable levels greater than 0.8 mg kg-in field trials on Australian soils. In field plot studies over 3 years on the effects of soil drainage conditions on the uptake of Cu and other trace elements by herbage (Berrow et al, 1983) a correlation coefficient of r = f0.67 was obtained between the mean Cu contents of nine samples of grass dominant mixed herbage and the corresponding EDTA-extractable soil Cu levels.…”
Section: Copper Deficiencymentioning
confidence: 98%
“…It was noticed also that there were no significant interaction affecting its concentration in leaves. Reith (1968) compared soil application and foliar application of CuSO 4 .5H 2 O and found that foliar application was less effective than a soil application. He stated that the difference in effects on plant composition could have been due to dilution effect.…”
Section: Vegetative Character Measurementsmentioning
confidence: 99%